Physicochemical and antioxidant properties of rice cooked with different proportions of black soybeans and cooking methods. Issue 6 (11th September 2018) - Lee, Ji Hae; Kim, Hyun‐Joo; Lee, Byong Won; Lee, Yu Young; Lee, Byoung Kyu; Ko, Jee Yeon; Woo, Koan Sik
Abstract: We compared the quality and physicochemical characteristics of rice cooked with different proportions (0%, 5%, 10%, 15%, and 20%) of un‐hulled and hulled black soybeans prepared using normal and high‐pressure rice cookers, with and without added alcohol. The water‐binding capacity and swelling power decreased upon adding un‐hulled black soybeans, but the water solubility increased. The swelling power decreased as more hulled black soybeans were added, but the water‐binding capacity and water solubility increased. The peak, trough, breakdown, final, and setback viscosities decreased upon adding black soybeans. The total polyphenol and flavonoid contents increased after adding black soybeans. The predominant phenolic acids in the rice/black soybean mixtures were protocatechuic acid and p‐coumaric acid. The 1, 1‐diphenyl‐2‐picrylhydrazyl ‐ and 2, 2‐azinobis(3‐ethyl benzothiazoline)‐6‐sulfonic acid (ABTS)‐radical‐scavenging activities increased upon adding black soybeans. We report the antioxidative properties of rice/black soybean mixtures prepared in different ways. These data should aid manufacturers. Practical applications: Cooked rice/black soybean mixtures can help to improve the health of Asian people who consume rice. Adding small amounts of alcohol during rice cooking also has a significant effect on the amount of phenolic compounds and antioxidant activity. When rice/black soybean mixtures were cooked in high‐pressure rice cookers, the radical‐scavenging activity was high. Such cookers can be used for industrial applications.